Motivation And Physical Activity: Correlation Study on Extracurricular Sports of High School Students - Oktadinata, Alek; Prabowo, Bangkit Yudo; Daya, Wawan Junresti; Diana, Fitri; Nugraha, Ugi; Melinda, Melinda; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
Problems arise when students feel less enthusiastic about extracurricular sports activities. This is an indication of the quality of physical activity. This research is a correlational research aimed at finding out whether there is a relationship between motivation and physical activity of students who take part in extracurricular sports at State High School 8 Merangin. This research method uses a quantitative descriptive method. The population in this study was class X extracurricular sports students at State High School 8 Merangin, totaling 118 students. Determining the sample in this study used a simple random sampling technique using the Slovin formula to obtain a sample of 33 students. Data collection used a motivation questionnaire and the international physical activity questionnaire (IPAQ). Based on the results of the data, the overall relationship between motivation and physical activity has a correlation coefficient value of (0.391) in the strong category, the relationship between intrinsic motivation and physical activity has a correlation coefficient value of (0.407) in the strong category and the relationship between extrinsic motivation and physical activity has a correlation coefficient value of (0.135). in the weak category. The conclusion illustrates that there is a positive relationship between motivation and extracurricular sports activities of students at State High School 8 Merangin in the strong category.